Rodovias de pedágio aberto ou free-flow: perspectivas para a implantação no Brasil - Saulo Horta Barbosa (2013)
In Brazil, the expansion of concession programs shows a tendency to finance roads by charging users directly. Although promoting substantial improvement in the conservation / operation of highways, concessions programs have always been questioned in relation to tariffs values. Searching for a more equitable tolling model, technological advances in charging systems have been employed around the world. Systems for automatic vehicle identification (AVI) already allow tolling on urban passages with high traffic volumes, or even charge users a fee which is proportional to the distance traveled. Thus, it becomes possible to reduce the basic toll amount without changing the financial balance of the concession, making its acceptance easier to users. Besides bringing benefits that are generated by automatic fee collection, Open Road Tolling (ORT) systems eliminate the need to stop the vehicle at toll plazas. In this context, this paper analyzes and describes the operation of Open Road Tolling systems (or free-flow) and the possibility to use them as a tool to promote pricing modicity and equity in Brazil. At first, this research brings an overview of the legal and socio-economic environment of road concessions in Brazil, in order to verify possible benefits and existing barriers to the development of ORT systems in the country. The Brazilian experience is then compared to previous international ones. This study also points out measures taken in Brazil to enable the operation of these systems, such as SINIAV and the program "Ponto-a-Ponto", and the main remaining obstacles to its effective enforcement. At last, it is performed a national case study through a digital simulation model built in software TransCAD. In a hypothetical scenario, the implementation of a free-flow system on the road MG-050 is built in order to investigate potential impacts on its demand.